2021
DOI: 10.1038/s42003-021-02329-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant-soil feedbacks help explain biodiversity-productivity relationships

Abstract: Species-rich plant communities can produce twice as much aboveground biomass as monocultures, but the mechanisms remain unresolved. We tested whether plant-soil feedbacks (PSFs) can help explain these biodiversity-productivity relationships. Using a 16-species, factorial field experiment we found that plants created soils that changed subsequent plant growth by 27% and that this effect increased over time. When incorporated into simulation models, these PSFs improved predictions of plant community growth and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…In the field, where stress, competition, and herbivory were present, we found that plant–soil feedbacks represented 14% of the total overyielding observed in experimental communities, compared with the 37% observed in this study. Results were broadly consistent with a paired field experiment, therefore providing clear support for PSFs as one of several mechanisms that determine the diversity–productivity relationship (Forero et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In the field, where stress, competition, and herbivory were present, we found that plant–soil feedbacks represented 14% of the total overyielding observed in experimental communities, compared with the 37% observed in this study. Results were broadly consistent with a paired field experiment, therefore providing clear support for PSFs as one of several mechanisms that determine the diversity–productivity relationship (Forero et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…In both the greenhouse and the field, PSFs improved Null model predictions of plant community biomass. Furthermore, both PSF and Null model predictions from this greenhouse experiment were correlated with community biomass in the field experiment (Forero et al, 2021). Taken together, results suggested that both plant community composition and PSFs are highly variable in time and space, but that overyielding is common and that PSFs help explain overyielding.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our results for net diversity effects imply that current drought events and plant-driven mechanisms have a greater impact on linkages between plant species richness and ecosystem functioning than do drought soil legacy effects. Nevertheless, the additive effects of drought soil legacy on net diversity effects support recent assertions that knowledge of plant-soil interactions can improve predictions of plant community growth and diversity-productivity relationships ( 14 , 66 ).…”
Section: Discussionmentioning
confidence: 63%
“…Wills et al, 2006). A likely reason why terrestrial plant communities are so diverse and resilient to environmental variability is the prevalence of negative plant-soil feedbacks (Forero et al, 2021). The climatic driver that has been studied most in relation to plant-soil feedbacks is drought (Beals et al, 2020).…”
Section: Direction Of Plant-soil Feedback Determines Plant Responses ...mentioning
confidence: 99%